Mermaid Adaptation through Exploration of Scales in Party Fashion - Wa Ode Amalia; Mandhe Sekar Nurindah (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
The dynamic development of the fashion industry encourages designers to create works that are relevant to future trends through fashion forecasting. One of the predicted themes for the 2025-2026 period is fluidity, which describes free and flowing changes. This research aims to develop a party dress inspired by the mermaid theme and follow the 2025/2026 fashion forecasting trend. The method used in this research is a three-stage design, which consists of problem definition and research, creative exploration, and implementation. This research interprets the concept of fluidity through the exploration of visual and textural elements inspired by mythology. This Adaptation includes the use of color, fabric texture, and details such as scales to create a party dress that reflects the free-flowing mermaid theme in accordance with the concept of fluidity. The result of this research is expected to produce party wear that is not only luxurious and aesthetic but also reinforces the theme of fluidity as part of future fashion trends.